Analisis Settlement Timbunan Causeway dan Container Yard pada Pembangunan Terminal Multipurpose Labuhan Bajo di Manggarai Barat, Nusa Tenggara Timur - Yerry Kahaditu Firmansyah (Jurnal TESLINK : Teknik Sipil dan Lingkungan, 2023)
The Labuhan Bajo Multipurpose Terminal, located in West Manggarai, East Nusa Tenggara, has a very important strategic value as the main transportation hub for domestic and international trade. With the increasing demand for the efficient handling of cargo and passenger traffic, the construction of well-designed causeways and container yards is essential to ensure the terminal's long-term functionality and stability. The main objective of this study is to evaluate potential settlement patterns, identify potential risks associated with soil deformation, and propose appropriate mitigation measures to ensure safe and sustainable operation of the terminal. The findings from this research explain the importance of a thorough settlement analysis in large-scale infrastructure projects, especially those involving causeways and container yards. By understanding the response potential of the soil and implementing effective mitigation measures, engineers, contractors and policy makers can increase the resilience of terminals, minimize adverse impacts and ensure their long-term viability.